(untitled) (Research, Society and Development, 2020)
Diabetic foot can be understood as the destruction of soft tissues, and as infections or ulcerations associated with neurological and vascular changes in the lower limbs of patients with Diabetes Mellitus (DM). It is also one of the most severe, costly, and devastating complications of DM, and foot ulcers are precursors of lower limb amputations in 85% of the cases. Thus, honey emerges as an alternative treatment which is economical, presents a low risk of bacterial resistance, and is widely available, indispensable factors for the continuity of treatment by the patients. This article is a scoping review with the objective of describing the evidence to elucidate the benefits of honey in the treatment of diabetic foot. The research includes primary studies, reviews, meta-analyses and/or meta-syntheses, books and guidelines, theses, and dissertations, published in indexed sources or in the gray literature published in the following databases: Scielo, LILACS, Pubmed, The Cochrane Library, Web of Science, SCOPUS, CINAHL, and Academic Search Premier, CAPS, the USP Digital Library of Theses and Dissertations, and the USP Integrated Search Portal. In the literature reviewed, 33 different benefits have been found which are described for the use of honey. Among these benefits, the higher healing rate and anti-microbial, anti-inflammatory, and debriding properties stand out, among others. Therefore, the analyzed studies showed a wide variety of benefits, which reflects the complexity of the action and the usefulness of this product.